Low-carbon optimal operation of distributed energy systems in the context of electricity supply restriction and carbon tax policy: A fully decentralized energy dispatch strategy. (10th April 2023) - Zhang, Sen; Hu, Weihao; Du, Jialin; Bai, Chunguang; Liu, Wen; Chen, Zhe
Abstract: The peer-to-peer energy sharing of distributed energy systems supports carbon neutrality targets by promoting self-sufficient local energy systems, energy saving and carbon emission reduction. This paper constructs a multi-energy sharing model to maximize the social welfare of distributed energy systems as the objective function. A marginal cost-based multi-energy pricing mechanism is introduced to fairly and appropriately identify the price of energy transactions among distributed energy systems. Besides, energy-consuming rights and carbon tax policies incentivize low-carbon dispatch of distributed energy systems by enforcing electricity supply restrictions and carbon emission constraints. Finally, a fully decentralized solution to the multi-energy sharing problem is achieved by exchanging energy trading price information and combining it with the dual consensus alternating direction multiplier method algorithm. The case study results show that the proposed multi-energy sharing framework achieves economic operation and low-carbon management of distributed energy systems and generates promising economic and environmental benefits compared to the traditional no-energy sharing paradigm, reducing the cost by 14.14% and carbon emission by 14.76%. Highlights: The optimal dispatch of DESs under low-carbon and power supply constraints is studied. A fully decentralized multi-energy sharing framework is developed. A marginal cost-based energy pricing mechanism is proposed. Using the DC - ADMM algorithm completely decentralized to solve the problem.